(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to assess the effect of adding flavoring agents to fermented cassava pulp (FCPU) on nutrient utilization, ruminal fermentation characteristics, and blood metabolites in growing cattle. Materials and Methods: A duplicated 3 × 3 Latin square design was randomly assigned to six growing beef cattle. Treatments were: 1) untreated FCPU (control), 2) 0.05% w/v vanilla-flavored FCPU, and 3) 0.05% w/v amyl acetate-flavored FCPU. Results: The results showed that flavoring agents did not affect dry matter intake (DMI) or digestibility of nutrients. Rumen pH and ammonia nitrogen concentrations did not change all treatments post feeding. Flavoring added to FCPU after feeding did not affect total volatile fatty acid (VFA) or VFA percentage. However, propionic acid levels tended to be lower in the vanilla-flavored FCPU group than those in the unflavored FCPU group at 0 h post feeding (p < 0.01). Growing bulls fed vanilla-flavored FCPU tended to have greater fungal zoospores in the rumen than those fed amyl acetate-flavored FCPU (p < 0.1) at 2 h after feeding. Dietary treatments did not affect blood glucose and urea nitrogen concentrations (p > 0.05). However, blood triglyceride concentration was greater for cattle fed a control diet than other treatments at 0 h post feeding (p < 0.05) and tended to be higher than those fed vanilla-flavored FCPU at 2 h after feeding (p < 0.1). Conclusion: It was suggested that adding vanilla or amyl acetate flavor to the FCPU showed no adverse effects on ruminal fermentation, blood metabolites, or nutritional digestibility; however, it did not increase DMI. J. Adv. Vet. Anim. Res., 10(3): 437–448, September 2023 http://doi.org/10.5455/javar.2023.j697